Gendered violence in Art: a study of Baroque and Classical Ages - Dharmani, Rishya (Talenta Publisher, 2022)
Art and history are always mirrors of each other. Their specific modes of functioning, despite being dissimilar to each other, are still consonant. Consciousness of time is common to them, traveling continuously through the past and future, creating the present. But art; its representation, subversion, methods, spaces, humans and life is sometimes contrarian to the march of history. Art often defies history by rejecting the 'present' and creating its own utopia.